Spontaneous Heterotopic Pregnancy: Dual Case Report and Review of Literature. (19th June 2016) - Chadee, Annika; Rezai, Shadi; Kirby, Catherine; Chadwick, Ekaterina; Gottimukkala, Sri; Hamaoui, Abraham; Stankovich, Vasiliy; Hale, Theodore; Gilak, Hamid; Momtaz, Mohammad; Sasken, Harvey; Henderson, Cassandra E.
Abstract : Introduction. Heterotopic pregnancy is a rare complication usually seen in populations at risk for ectopic pregnancy or those undergoing fertility treatments. It is a potentially dangerous condition occurring in only 1 in 30, 000 spontaneous pregnancies. With the advent of Assisted Reproduction Techniques (ART) and ovulation induction, the overall incidence of heterotopic pregnancy has risen to approximately 1 in 3, 900 pregnancies. Other risk factors include a history of pelvic inflammatory disease (PID), tubal damage, pelvic surgery, uterine Mullerian abnormalities, and prior tubal surgery. Heterotopic pregnancy is a potentially fatal condition, rarely occurring in natural conception cycles. Most commonly, heterotopic pregnancy is diagnosed at the time of rupture when surgical management is required. Case. This paper represents two cases of heterotopic pregnancies as well as a literature review. Conclusion. Heterotopic pregnancy should be suspected in patients with an adnexal mass, even in the absence of risk factors. Clinicians must be alert to the fact that confirming an intrauterine pregnancy clinically or by ultrasound does not exclude the coexistence of an ectopic pregnancy. A high index of suspicion in women is needed for early and timely diagnosis, and management with laparotomy or laparoscopy can result in a favorable and successful obstetrical outcome.